Emergence of New Segments of Swiss Wine Consumers: A Comparison with a Segmentation Study from 2011 - Thomas A. Brunner; Thomas Schnetzer; Mathilde Delley (Australian Journal of Grape and Wine Research)
This study aimed to examine the various Swiss wine consumer segments, evaluate whether and how these segments had changed during the past decade, and formulate recommendations for targeted marketing. Data were collected through an online survey involving randomly selected Swiss households who were invited using flyers; the final sample size was N = 512. With the use of a shortened version of the questionnaire devised for a similar study published in 2011, we were able to compare the results of the said study with the present results. The results of the principal component analyses revealed eight factors. The factor scores were then used in hierarchical cluster analyses, which in turn revealed seven distinct segments of wine consumers. Four of these had already been identified 10 years ago: involved (21.9%), price-conscious (20.3%), lowbrow (16.0%), and image-oriented (5.3%) consumers. Three new segments emerged: local (15.2%), traditional (11.9%), and relaxation-seeking (9.4%) consumers. Our results show that each wine seller has its own place in the market and can benefit from the present study, which determines the appropriate marketing mix for a specific segment.